(Network value)‐based adaptive dynamic bandwidth allocation algorithm for 5G network slicing. Issue 3 (25th December 2022) - Wu, Lijuan; Gan, Chaoqin; Xu, Zhongsen; Hui, Jianqiang
Abstract: In this article, a (network value)‐based inter‐slice and intra‐slice adaptive dynamic bandwidth allocation algorithm is proposed for the coexistence scenario of URLLC slices, eMBB slices, and mMTC slices in 5G fronthaul networks. The network value model applicable to network slicing is constructed to provide a means for the value evaluation of virtual networks. According to the bandwidth requirements of the slices, the adaptive inter‐slice bandwidth allocation is realized to ensure that the fronthaul network can obtain the maximum economic value under different load states. For the service characteristics of three slices, three intra‐slice bandwidth allocation algorithms are proposed, respectively, to realize adaptive ONU bandwidth allocation. It not only meets the differentiated service demands of different slices, but also enables each slice to obtain the maximum QoS value. By simulation and analysis, the effectiveness of the proposed algorithm is demonstrated. Abstract : In this article, an inter‐slice and intra‐slice adaptive dynamic bandwidth allocation algorithm is proposed based on network value model for 5G fronthaul network. Through this algorithm, the network can obtain the maximum QoS value and the maximum economic value.